RECLAIMING AGENCY AND APPRECIATING LIMITS IN TEACHER EDUCATION: EXISTENTIAL, ETHICAL, AND PSYCHOANALYTICAL READINGS - Phelan, Anne; Hansen, Dion (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2018)
A basic premise of teacher education is the value of teacher agency, that is, the teacher’s capacity to take responsibility for one’s knowledge, beliefs, judgements, and relationships. How can teacher educators sustain a commitment to agency in light of critiques of western modernity, specifically in relation to the existence of a rational autonomous subject, the erasure of history, and the opacity of language? Drawing on existentialism, ethics, and psychoanalysis, we discuss three practicum vignettes to illustrate what we are calling “the chiastic complexity” of agency within the field of teacher education. We argue that admission of the limits of teacher agency may be the source of ethical insight, educational opportunity, and political resistance for student teachers and teacher educators.